Neisseria gonorrhoeae Challenge Increases Matrix Metalloproteinase-8 Expression in Fallopian Tube Explants - Juica, Natalia E.; Rodas, Paula I.; Solar, Paula; Borda, Paula; Vargas, Renato; Muñoz, Cristobal; Paredes, Rodolfo; Christodoulides, Myron; Velasquez, Luis A. (Frontiers in Cellular and Infection Microbiology, 2017)
Background:Neisseria gonorrhoeae (Ngo) is the etiological agent of gonorrhea, a sexually transmitted infection that initially infects the female lower genital tract. In untreated women, the bacteria can ascend to the upper genital reproductive tract and infect the fallopian tube (FTs), which is associated with salpingitis and can lead to impaired FT function and infertility. The extracellular matrix (ECM) plays an important role in cell migration and differentiation in the female genital tract, and some pathogens modify the ECM to establish successful infections. The ECM is regulated by matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs), their endogenous inhibitors; MMP deregulation causes pathological conditions in a variety of tissues. Results: The aim of this work was to analyze the expression and localization of MMP-3, MMP-8, MMP-9, and TIMP-1 in FT explants during Ngo infection using real-time PCR, immunohistochemistry, zymography and ELISA. No significant variations in MMP-3, MMP-9, and TIMP-1 transcript levels were observed. In contrast, a significant increase (p < 0.05) was observed for MMP-8 expression and was accompanied by stromal immunoreactivity in infected explants. ELISA results supported these findings and showed that MMP-8 release increased upon gonococcal infection. Conclusions: Our results indicate that gonococcal infection induces increased MMP-8 expression, which might contribute to FT damage during infection.